Penerapan Metode Fuzzy Sugeno Untuk Menentukan Kelayakan Pengiriman Limbah Barang Berbahaya Dan Beracun - Alfannisa Annurrallah Fajrin; Tukino Tukino (LPPM Universitas Putera Batam, 2023)
PT Semesta Citra Alam Batam is engaged in waste management and is located in the city of Batam. The waste collected by PT Semesta Citra Alam Batam is gathered at a waste collection warehouse located in the Industrial Waste Management Area of Batam City. The collected waste must be transported to waste utilization or hazardous waste disposal facilities. The data collection technique in this research is through observation and interviews conducted at PT Semesta Citra Alam Batam. The data analysis method used is fuzzy logic with the Sugeno method, which involves four stages: fuzzification, forming a fuzzy knowledge base, inference engine, and defuzzification. The research results from the application of fuzzy logic to determine the shipment of hazardous waste (B3 waste) at PT Semesta Citra Alam Batam involve both input and output variables. The input variables consist of load, content, and the output variable is a decision made using Matlab. These variables will generate rules that will be used to determine whether to send the waste or not.